APPLICATION OF ISLAMIC ECONOMIC PRINCIPLES IN REALIZING MANAGEMENT BANKING WITHOUT INTEREST - Suharli Suharli; Abdul Wahab; Abdul Hamid Habbe (Dinasti Publisher, 2021)
The emergence of the Islamic Economic System through Islamic Banking is expected to be a solution in the economic world. This paper purpose to review the principles of Islamic banking management without interest. The method used in this paper is a scientific study approach with library research, with data collection through a study of books, literature, notes, and various reports related to the problem to be solved. The results of the study found that the banking sector in the Islamic economy does not recognize interest rate instruments. The Islamic financial system applies profit and loss sharing, not to interest which has determined the profit level in advance. This Islamic economic value is implemented in Islamic banks and is based on three aspectsnamely aspects of faith, aspects of Sharia and aspects of morality. Islamic banking must also always refer to Islamic principles, namely Justice, Partnership, Transparency, and Universal.